2011
DOI: 10.3233/jad-2010-101518
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Pattern in Blood for the Early Detection of Alzheimer's Disease

Abstract: A whole genome screen was performed using oligonucleotide microarray analysis on blood from a large clinical cohort of Alzheimer's disease (AD) patients and control subjects as clinical sample. Blood samples for total RNA extraction were collected in PAXgene tubes, and gene expression analysis performed on the AB1700 Whole Genome Survey Microarrays. When comparing the gene expression of 94 AD patients and 94 cognitive healthy controls, a Jackknife gene selection based method and Partial Least Square Regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 29 publications
4
77
0
Order By: Relevance
“…This test detects the blood-based gene expression signature in blood samples and adopts a combination of multiple gene expression assays to obtain a prediction value for disease classification. Alterations in a gene expression signature in peripheral blood are postulated as a result of a systemic disease response in AD as verified by many previous studies [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…This test detects the blood-based gene expression signature in blood samples and adopts a combination of multiple gene expression assays to obtain a prediction value for disease classification. Alterations in a gene expression signature in peripheral blood are postulated as a result of a systemic disease response in AD as verified by many previous studies [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 80%
“…For product development, further adaptation of the qPCR protocol for regulatory approval purposes is planned prior to locking of the algorithm; moreover a larger number of assays into the optimization phase is preferred. However, in this study we wanted to investigate a subset of 20 informative assays that we have previously identified in independent in-house studies (results not shown) during the development of ADtect ® [34,35]. The identification of these assays was based on the discrimination of AD and cognitively healthy controls.…”
Section: Prediction Of MCI That Evolves Into Ad Dementia Within Two Ymentioning
confidence: 99%
See 2 more Smart Citations
“…Such approach was already tested in DS and different pathologies. [9][10][11][12] The low number of patients, especially in the IQ À group, was secondary to the fact that we wanted to restrict this study only to the T21 patients that we could discriminate by IQ test. Interestingly, the group IQ À was predominantly males, whereas the IQ þ group was frequently females with a sex ratio of 2/3.…”
Section: Discussionmentioning
confidence: 99%